Glycolytic control of adjuvant-induced macrophage survival: Role of PI3K, MEK1/2, and Bcl-2 - Chang, M.; Hamilton, J.; Scholz, G.; Elsegood, Caryn (Society for Leukocyte Biology, 2009)
Uptake by macrophages forms an important part of the mode of action of particulate adjuvants such as oil-in-water emulsions and alum. We have found previously that such adjuvants promote macrophage survival and suggested that this response may contribute to their efficacy. To explore this adjuvant activity further, we have investigated whether oil-in-water emulsion stimulates glucose uptake in macrophages and whether such uptake is relevant to the promotion of survival. We found that oil-in-water emulsion stimulated glucose uptake in a biphasic manner. The first acute phase was independent of mRNA and protein synthesis but appeared to require PI3K activity. In contrast, the second chronic phase was dependent on mRNA and protein synthesis. Importantly, the second phase of glucose uptake required MEK1/2 as well as PI3K activity, indicating that the MEK1/2 pathway can also contribute to cellular glucose uptake. The increased glucose transporter 1 expression during the second phase and long-term survival also appeared to be dependent on PI3K and MEK1/2 signaling pathways. Metabolism of the glucose was required for the emulsion-stimulated survival as well as the increase of prosurvival Bcl-2 transcript levels and maintenance of Bcl-2 protein expression. As transgenic overexpression of Bcl-2 enhances the survival of macrophages in the absence of growth factor, the glycolytic control of Bcl-2 levels may play a central role in emulsionstimulated macrophage survival. Enhanced glucose uptake by macrophages may therefore be critical to the action of particulate adjuvants. © Society for Leukocyte Biology.